2022
DOI: 10.1021/acs.jmedchem.2c00662
|View full text |Cite
|
Sign up to set email alerts
|

GNE-064: A Potent, Selective, and Orally Bioavailable Chemical Probe for the Bromodomains of SMARCA2 and SMARCA4 and the Fifth Bromodomain of PBRM1

Abstract: Bromodomains are acetyllysine recognition domains present in a variety of human proteins. Bromodomains also bind small molecules that compete with acetyllysine, and therefore bromodomains have been targets for drug discovery efforts. Highly potent and selective ligands with good cellular permeability have been proposed as chemical probes for use in exploring the functions of many of the bromodomain proteins. We report here the discovery of a class of such inhibitors targeting the family VIII bromodomains of SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 31 publications
(88 reference statements)
1
39
1
Order By: Relevance
“…Binding to the other family members is much less sensitive to the methyl stereochemistry: either R-or S-methyl is modestly deleterious compared to the unsubstituted piperidine. Acyl piperazine analogues such as 5 and 6 bind tightly to subgroup 2 domains, 39,44 and analogues 15 and 16 that include a methyl group positioned as in 10 retain this characteristic (Table 1). Although 16 is not selective for PBRM1(2), the affinity for this domain was enhanced more than 5-fold by the shift in the position of the methyl group 2) screen compared to previously determined SMARCA4 bromodomain IC 50 s. 43 The magenta point represents GNE-064 (6), 39 while the PBRM1(2)-selective compounds 10 and 11 are indicated in light blue.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding to the other family members is much less sensitive to the methyl stereochemistry: either R-or S-methyl is modestly deleterious compared to the unsubstituted piperidine. Acyl piperazine analogues such as 5 and 6 bind tightly to subgroup 2 domains, 39,44 and analogues 15 and 16 that include a methyl group positioned as in 10 retain this characteristic (Table 1). Although 16 is not selective for PBRM1(2), the affinity for this domain was enhanced more than 5-fold by the shift in the position of the methyl group 2) screen compared to previously determined SMARCA4 bromodomain IC 50 s. 43 The magenta point represents GNE-064 (6), 39 while the PBRM1(2)-selective compounds 10 and 11 are indicated in light blue.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It can be seen from the overlay that the phenolic oxygen of 13 is a surrogate for W1. 39 One way in which the furyl group could be accommodated in the position shown would be for W1 to remain and to engage in a hydrogen bond to the furyl oxygen as depicted. (It seems likely in this model that W2 would be displaced.)…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…72,73 However, PFI-3 confirmed that a ligandable binding site in BRG1/BRM bromodomain existed which went on to catalyze further hypotheses around degradation of sub-unit components; 74 ATPase domain inhibitors have also followed. 75,76…”
Section: Pfizermentioning
confidence: 99%
“…The BRG1-associated factor (BAF) complexes function as ATP-dependent chromatin remodelers and consist of three biochemically distinct complexes: canonical BAF (cBAF), polybromo-associated BAF (PBAF), and GLTSCR1/like-containing BAF (GBAF or ncBAF) (Figure A). All three types of BAF complexes share the ATPase and several core subunits but also contain unique subunits. BAF complexes are the most frequently mutated chromatin remodeling complex in cancer, and different subunits, in cooperation with the catalytic subunits BRM and BRG1, play crucial roles in regulating chromatin accessibility. Multiple compounds have been developed to target BAF complex subunits, including small molecules and proteolysis targeting chimeras (PROTACs); however, most of the subunits have yet to be explored as targets in disease. …”
Section: Introductionmentioning
confidence: 99%